ANALYSIS OF THE EFFECT OF PUBLIC SHARE OWNERSHIP, PROFITABILITY, LEVERAGE AND LIQUIDITY ON COMPANY VALUE (STUDY OF MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2017-2021 PERIOD) - Mohamad Nugroho; Astrid Dita Meirina Hakim (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
This study aims to determine the effect of Public Share Ownership on Company Value, Profitability on Company Value, Leverage on Company Value, and Liquidity on Company Value in mining companies listed on the Indonesia Stock Exchange 2017-2021 Period. Using the Non Probability Sampling technique using the Purposive Sampling method. The population in this study were 44 mining companies listed on the Indonesia Stock Exchange for the 2017- 2021 period and the sample used in this study were 13 mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research was conducted using multiple linear regression methods assisted by the E-views 10 program and Microsoft Excel 2016. The results showed that Public Share Ownership had no effect on Firm Value due to the number significance higher that 0.005 about 0,4579, Profitability had no effect on Firm Value due to the number significance higher that 0.005 about 0,8998  , Leverage had significance effect on Firm Value due to the number significance  lower than 0.005 about 0,0336 , and Liquidity had  no significance effect to Company Value due to the number significance  higher than 0.005 about  0,06631.Keywords: Public Shareholding, Profitability, Leverage, Liquidity, Firm Value